A descriptive analysis of sarcopenia markers in young adults with down syndrome - Brett S. Nickerson; Michael R. Esco; George Schaefer; Elroy J. Aguiar; Stefan A. Czerwinski (Experimental Gerontology)
Background: Most body composition research in individuals with Down Syndrome (DS) has focused on overweight and obesity. Although limited research has shown muscle mass indexes and physical performance levels of adults with DS are similar to or lower than older adults with sarcopenia, there is still a large gap in the literature regarding sarcopenia. Objective: This brief report provides a comprehensive descriptive analysis of sarcopenia and obesity markers in individuals with DS. Methods: Fourteen young adults (age = 26 ± 9 yrs.) with DS (males: n = 6; females: n = 8) had appendicular skeletal muscle mass (ASM) measured with bioimpedance analysis and handgrip strength (HGS) measured with a hand dynamometer (dominant hand). Sarcopenia was computed using the European Working Group on Sarcopenia in Older People revised definition (EWGSOP2). Results: The BMI for the entire group was 24.41 ± 4.01 kg/m2, ranging from 16.21 to 31.31 kg/m2, with one participant classified as obese. ASM ranged from 11.33 to 24.41 kg (17.49 ± 4.71 kg), and 64 % of participants fell below the EWGSOP2 criteria for muscle mass. HGS ranged from 8 to 31 kg (20 ± 7 kg), and 57 % of participants fell below the EWGSOP2 criteria for muscular strength. Lastly, 5 of 14 participants (approximately 36 %) had sarcopenia according to the EWGSOP2 definition. Conclusion: An alarming number of young adults with DS had sarcopenia, and low HGS and ASM when using the EWGSOP2 definition. Health professionals are encouraged to screen for sarcopenia in young adulthood rather than deferring it to a later stage in life for individuals with DS.